A Comparative Study of Airfoil Stall Characteristics Based on Detached Eddy Simulation Incorporated with Weighted Essentially Non-Oscillatory Scheme and Weighted Compact Nonlinear Scheme - Yan Qi; Bowen Zhong; Song Zou (Aerospace)
In this paper, the detached eddy simulation (DES) method is used to calculate the aerodynamic characteristics of NACA0015 airfoil by combining the Riemann approximate solution HLLC (Harten–Lax–van Leer Contact) with the high-order weighted essentially non-oscillatory (WENO) scheme and the weighted compact nonlinear scheme (WCNS), respectively. By comparing the calculation results of the two different numerical schemes with the wind tunnel test results, it is found that both numerical schemes can accurately calculate the aerodynamic parameters at small angles of attack. However, in the range of near-stall angle (in the range of 10–15°), the calculation results of various numerical schemes have a certain degree of deviation. The calculation results of the fifth-order WCNS and the fifth-order WENO scheme are closer to the experimental values. The fifth-order WCNS predicts the stall angle of attack more accurately than the fifth-order WENO scheme. The calculation accuracy of the fifth-order WCNS is better than that of the fifth-order WENO scheme under the post-stall condition (where the angle of attack is greater than 15°). By comparing the vorticity contours calculated by different numerical schemes, it is found that the numerical dissipation of the fifth-order accuracy is smaller than that of the third-order accuracy, and the vortex capture ability is stronger. WCNS captures the small vortex structure that the WENO scheme does not.